1998
DOI: 10.1046/j.1365-2958.1998.00677.x
|View full text |Cite
|
Sign up to set email alerts
|

Formation of oligomeric rings by XcpQ and PilQ, which are involved in protein transport across the outer membrane of Pseudomonas aeruginosa

Abstract: SummaryPseudomonas aeruginosa is able to translocate proteins across both membranes of the cell envelope. Many of these proteins are transported via the type II secretion pathway and adopt their tertiary conformation in the periplasm, which implies the presence of a large transport channel in the outer membrane. The outer membrane protein, XcpQ, which is involved in transport of folded proteins across the outer membrane of P. aeruginosa, was purified as a highly stable homomultimer. Insertion and deletion muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

10
189
0
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(200 citation statements)
references
References 49 publications
10
189
0
1
Order By: Relevance
“…There has been a long series of papers building our understanding of secretin structure that probably originated from the first observation of very-low-resolution EM images of ring-shaped structure for YscC (T3SS), XcpQ (T2SS), and PilQ (T4PS) (7,8). Slowly but convincingly, it was shown that secretins are large homo-oligomeric assemblies of 12 to 16 monomers forming a distinctive bipartite ring-shaped and cylindrical structure on their C-and N-terminal sides, respectively.…”
mentioning
confidence: 99%
“…There has been a long series of papers building our understanding of secretin structure that probably originated from the first observation of very-low-resolution EM images of ring-shaped structure for YscC (T3SS), XcpQ (T2SS), and PilQ (T4PS) (7,8). Slowly but convincingly, it was shown that secretins are large homo-oligomeric assemblies of 12 to 16 monomers forming a distinctive bipartite ring-shaped and cylindrical structure on their C-and N-terminal sides, respectively.…”
mentioning
confidence: 99%
“…This OM component belongs to a family of proteins generically designated as secretins (6). This family also includes members that are involved in type III protein secretion (T3SS), type IV pilus assembly, type IV bundle-forming pili, toxin co-regulated pili, and assembly and export of filamentous phage (7)(8)(9)(10)(11)(12). Therefore, secretins constitute an important group of transporters specialized in the translocation of bulky macromolecules or macromolecular complexes across the OM.…”
mentioning
confidence: 99%
“…Several secretins have been purified and analyzed by electron microscopy, revealing that 12-14 identical secretin monomers form ring-like complexes with a central channel large enough to accommodate their substrates (7,(13)(14). The homology between the members of the secretin family is contained within the C-terminal half of the protein (see Fig.…”
mentioning
confidence: 99%
“…Single particle analysis of the same detergent-solubilized material identified a putative C8 rotational symmetry, suggesting that the Wza⅐His 6 complex is octameric (13). At a gross structural level, Wza multimers resemble the secretins such as PilQ (18), pIV (19), PulD (20), XcpQ (21), and YscC (22), which export proteins in Neisseria sp., Pseudomonas aeruginosa, Klebsiella oxytoca, P. aeruginosa, and Yersinia sp., respectively. However, these similarities do not extend to the primary sequence features (13).…”
mentioning
confidence: 99%